SUBER IMPROVING CACHE MEMORY POWER - Sabar Peringatan; Ir. Irwan Nimara, MMSI (Jurnal Sistem Komputer, 2002)
Memory access time is the time interval between the start issuing a request to memory when the information is complete and transferred from the memory that is accessed. Â The same thing applies for an access operation that required additional time to remove words that have been written into the cache memory to the memory can be eliminated by applying the write through.